Penerapan AI Melalui Pendekatan Heuristik Semilaritas Pada Game Edukasi Anak Usia Dini - Rendy Jemi Sahputra; Ari Muzakir (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
Game is one of the rapidly growing industries in everyday life. Currently the game is very popular in all circles, both among children, teenagers and adults. However, there are still many games that only prioritize addictive elements and ignore educational elements. Therefore, here the author will build a game that has an educational element as a learning medium. This study will apply AI to an early childhood educational game through a heuristic semilarity approach to the habits of early childhood in answering questions such as equating in everyday life. This research will produce a game that can improve intelligence, creativity and memory at an early age such as guessing pictures, counting and arranging words randomly.